The Ability of English Teachers in Implementing the 2013 Curriculum at SMK Negeri 1 Kendari - Kasmawati Kasmawati; Sartiah Yusran; Sahlan Sahlan (Journal of Language Education and Educational Technology (JLEET), 2019)
This study aimed to find out the extent of ability of English teachers in implementing the 2013 curriculum at SMK Negeri 1 Kendari. This study applied a qualitative research method with descriptive approach. The respondences of this study were four English teachers at SMK Negeri 1 Kendari who have implemented the 2013 curriculum. The data was obtained by conducting observation, interview and documentation. The data was analyzed through four phases. They were data collection, data reduction, data presentation, and taking conclusion. The results of this study showed that in the aspect of planning of learning, English teachers have compiled an independent lesson plan, developed from the 2013 curriculum syllabus. This was indicated by the achievement value based on the APKG sheet results which was 90 and was categorized as very good. In the aspect of implementation of learning, the English teachers have applied a scientific approach. This was indicated by the achievement value based on APKG sheet results which was 87 and was categorized as very good. In the aspect of assessment of learning, teachers have implemented authentic assessments and follow-up learning outcomes. This was indicated by the achievement value based on the APKG sheet results which was 78 and was categorized as good.Keywords:English Teachers Ability; Implementation; 2013 Curriculum